Efforts for the production of liquid biofuels in Crete: bioethanol and biodiesel - Vourdoubas J. (Comprehensive economic and spatial bio-energy modelling, 2002)
The production of liquid biofuels in Greece has not been developed yet. Some efforts have been made for the production of bioethanol from sweet sorghum, but there is no industrial production at this moment in the country. Also, very few studies exist on the production of biodiesel today in Greece where the rape seed has not been cultivated yet. In this paper, the results of two research projects, which are taking place in Crete and are related to the production of bioethanol from carob and of biodiesel from waste cooking oils, are presented. These research projects have been funded by the E.C. through the ALTENER programme.
Seminar on Comprehensive Economic and Spatial Bio-Energy Modelling, 2001/06/07-08, Grignon (France)